Islamic Leadership Strategy in the Implementation of SPMI to Support the Sustainability of Educational Institutions - Wellaa Syamkhotsaa; Maksudin; Wulan Priyanggani (ADARA, 2026)
The implementation of the Internal Quality Assurance System (SPMI) in madrasas is often perceived as an administrative requirement, so it has not been fully developed into a sustainable quality culture. This condition requires leadership that integrates Islamic values, quality governance, and institutional sustainability. This study aims to analyze Islamic leadership strategies in implementing SPMI to support the sustainability of MI Miftahul Akhlaqiyah Semarang. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving the head of madrasah, deputy head, SPMI team, teachers, administrative staff, foundation representatives, school committee, parents, and students. Data analysis was conducted through data condensation, data display, and conclusion drawing, while data validity was ensured through triangulation and member checking. The findings show that the values of shiddiq, amanah, tabligh, and fathanah are operationalized through data transparency, task distribution, quality communication, deliberation, exemplary behavior, and needs-based decision-making. SPMI has been implemented through the cycle of standard setting, implementation, evaluation, control, and quality improvement, although documentation, evaluation indicators, and follow-up mechanisms still require strengthening. This study concludes that Islamic leadership functions as an integrative strategy for developing quality culture and madrasa sustainability. The implication is that madrasas need to strengthen value-based quality evaluation systems consistently, participatively, and systematically.